Simulação da transferência tridimensional de massa e calor empregando o método dos volumes finitos - Wisbiski, Eduardo Augusto Buss (2022)
Currently, the simulation of physical phenomena has great relevance for engineering. It allows predicting the behavior of systems and processes, without the limitations that real experimentation can provide. Some phenomena, such as mass and heat transfer, are greatly benefited from the simulation in a virtual environment, bringing assertiveness and reliability to the responses obtained in the program. These phenomena are manifested in nature and in numerous industrial operations, such as combustion, refrigeration, drying, cooking, among many others. A simultaneous application of these transfers on an industrial scale is verified during the extraction of cellulose from wood. In this process, there is a step of cooking small wood chip in an alkaline solution. After sufficient time at this stage, the wood components dissolve in the other chemical products used, forming a semi-solid pulp. This product is then converted into paper, which is widely versatile and even used in the production of packaging. The relevance of this sector for Brazil is accentuated, since the country occupies the second place in the world ranking of pulp producers, behind only the United States. This fact, combined with the occurrence of the transport phenomena mentioned in its process, justifies the relevance of research on this topic. In this sense, the objective of the present work was to predict the concentration field of water and temperature in a wooden cube during its cooking, modeling conditions used in the extraction of cellulose. The optimal number of volumes for the simulation was also determined, balancing maximum response precision with the appropriate computational effort. The finite volume method was used as a numerical tool, creating a resolution algorithm implemented in the MATLAB [trade mark] software, in its R2021b, Update 2 version. It is considered that the results were consistent, with faster reaching of equilibrium for the outermost regions of the wooden body, and slower for the innermost regions. Regarding the mesh independence test, it took 4.0 hours of simulation to balance the system with transfers in one dimension, with 24 being the ideal number of volumes. For the two-dimensional system, 1.7 hours of simulation were needed, with 576 being the best number of volumes. Finally, for the three-dimensional system, 1.2 hours were required, with 216 volumes being the mesh independence test response. It is considered that the simulation data are coherent when compared with literature values for laboratory experimentation. As future research, we suggest the evaluation of other chemical components present in the mass transfer (sodium hydroxide and sodium sulfite), in addition to water (moisture), which was the object of study of this work.